Ethnic conflicts in Georgia and the Russian position on it 1989- - Khairi Matroud Al-Kanani, Ali; Abd Ali Ghailan Al-Rubaiey, Hussein (Journal of College of Education, 2022)
The ethnic conflicts in Georgia extend to different eras, and came as a result of the accumulation of a number of factors, foremost of which was the great differences between the various ethnicities, linguistic cultural differences and ideological directions for all parties, as the nationalism that attempts to the stronger party in the equation imposed on the other parties, and among the important reasons is the shift in Russian power from one era to another, and thus this matter was reflected in the conflict area until the Georgian crisis was born due to the intervention of world powers in the region and led to the 2008 war between Georgia and the Russian Federation.